2016
DOI: 10.1002/cam4.771
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ubiquitin ligase RNF126 regulates the progression of tongue cancer

Abstract: This study aims to analyze the role of RNF126 in the oncogenesis of tongue cancer. The cell proliferation and viability of human tongue cancer cells, SCC25 and SCC9 cells, were determined by cell counting and MTT assay, respectively. The effect of RNF126 on regulating AKT signaling pathway was analyzed through western blotting. The transplantation tumor model of nude mice was used to evaluate the tumorigenecity of RNF126. Knockdown of RNF126 inhibited the proliferation and viability of SCC9 and SCC25 cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 17 publications
(21 reference statements)
2
25
0
Order By: Relevance
“…Therefore, we further determined the activation of AKT, the critical component of PI3K/AKT signal pathway. Although it has several phosphorylation sites, phosphorylation of Ser308 and Thr473 is the sign of AKT activation . Our results suggested that knockdown of MG53 significantly promoted the phosphorylation of AKT Ser308 and AKT Thr473 in SCC25 cells ( Figure ).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Therefore, we further determined the activation of AKT, the critical component of PI3K/AKT signal pathway. Although it has several phosphorylation sites, phosphorylation of Ser308 and Thr473 is the sign of AKT activation . Our results suggested that knockdown of MG53 significantly promoted the phosphorylation of AKT Ser308 and AKT Thr473 in SCC25 cells ( Figure ).…”
Section: Resultsmentioning
confidence: 57%
“…Cell Culture, Plasmid and RNAi Construction : Human tongue cancer cell lines, SCC9 and SCC25 cells, were cultured in complete DMEM medium which had 10% FBS and 1% Penicillin–Streptomycin. Mammalian expression plasmids, MG53 and MG53‐RNAi, were constructed with the same protocol of the previous report …”
Section: Methodsmentioning
confidence: 99%
“…A literature review of the other 5 targets showed that some of these genes have been previously studied in tumor diseases. RNF126 promotes the proliferation and viability of tongue cancer by regulating the AKT signaling pathway [ 36 ]. RNF126 was found to positively regulate BRCA1 by directly interacting with E2F1 for homologous recombination in breast and ovarian cancer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNF126 has been implicated in a number of physiological and pathological processes, such as cancer progression, membrane receptor trafficking, and immune response modulation. RNF126 was shown to ubiquitinate and promote the degradation of the tumor suppressor p21 ( Zhi et al., 2013 ) and to enhance the Akt signaling pathway ( Wang et al., 2016 ). Moreover, it was shown to regulate the endosomal sorting of the epidermal growth factor receptor (EGFR) ( Smith et al., 2013 ) and cation-independent mannose 6-phosphate receptor (CI-MPR) ( Smith and McGlade, 2014 ) and to induce ubiquitination of the activation-induced cytidine deaminase (AID), an enzyme involved in the process of antibody diversification in the immune system ( Delker et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%